Angiotensin II modulates THP-1-like macrophage phenotype and inflammatory signatures via angiotensin II type 1 receptor - Barhoumi, Tlili; Mansour, Fatmah A.; Jalouli, Maroua; Alamri, Hassan S.; Ali, Rizwan; Harrath, Abdel Halim; Aljumaa, Maha; Boudjelal, Mohamed (Frontiers in Cardiovascular Medicine, 2023)
Angiotensin II (Ang II) is a major component of the renin–angiotensin or renin–angiotensin–aldosterone system, which is the main element found to be involved in cardiopathology. Recently, long-term metabolomics studies have linked high levels of angiotensin plasma to inflammatory conditions such as coronary heart disease, obesity, and type 2 diabetes. Monocyte/macrophage cellular function and phenotype orchestrate the inflammatory response in various pathological conditions, most notably cardiometabolic disease. An activation of the Ang II system is usually associated with inflammation and cardiovascular disease; however, the direct effect on monocyte/macrophages has still not been well elucidated. Herein, we have evaluated the cellular effects of Ang II on THP-1-derived macrophages. Ang II stimulated the expression of markers involved in monocyte/macrophage cell differentiation (e.g., CD116), as well as adhesion, cell–cell interaction, chemotaxis, and phagocytosis (CD15, CD44, CD33, and CD49F). Yet, Ang II increased the expression of proinflammatory markers (HLA-DR, TNF-α, CD64, CD11c, and CD38) and decreased CD206 (mannose receptor), an M2 marker. Moreover, Ang II induced cytosolic calcium overload, increased reactive oxygen species, and arrested cells in the G1 phase. Most of these effects were induced via the angiotensin II type 1 receptor (AT1R). Collectively, our results provide new evidence in support of the effect of Ang II in inflammation associated with cardiometabolic diseases.